Characteristics of detrital chromian spinels in sandstones from the Nam Duk Formation, Amphoe Lom Sak and Amphoe Nam Nao, Changwat Phetchabun - Vichai Chutakositkanon (Chulalongkorn University, 1999)
151 pages